Peculiarities of grain technological indices establishment for coated and naked grain oats (Avena sativa L.) - О. І. Буняк (Plant Varieties Studying and Protection)
Oats technological indices have been analyzed. Influence of growing conditions on natural weight, kernel size, and hoodness is established. The study summary indicates essential dependence of natural weight and hoodness and precipitation at the stage of grain formation in coated grain oats varieties. Moisture supply in the period of grain formation essentially influenced the percentage of coated grains formation and natural weight score in naked grain varieties. Morphometric analyzes of oats caryopsis was completed using the method of machine vision. Correlation between technological indices and morphometric characteristics of naked and coated grain of oats was determined. Also, essential dependence of hoodness on 1000 seeds weight and the lack of essential correlation with morphometric characteristics of the calliopsis were established. Calliopsis width essentially influenced the weight of 1000 seeds. Metric indices of naked grain oats calliopsis exposed close correlation with kernel size and natural weight. Weight of 1000 seeds exposed essential varietal distinctness and was determined by genetic peculiarities of varieties